PERSEPSI AUDITOR BKM DENGAN PEMAKAI LAPORAN KEUANGAN BKM TENTANG EXPECTATION GAP DALAM HAL INDEPENDENSI, KOMPETENSI AUDITOR, PERAN DAN TANGGUNG JAWAB AUDITOR - Fakhrial Firdausy Alhaq (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research purpose to examine whether or not there’s a significant difference in perceptions between Auditor BKM with financial statement users in terms of independence, auditor competency, role and responsibilities of auditors. Methods used in this research is form of survey methods. Sampling was done using purposive sampling technique. The data used in this research is form of primary data through a survey questionnaire that was distributed directly to the respondents. Perceptions of respondents measured from the answers to the questions in the questionnaire using an interval size from Likert scale. Validity tests using the Pearson Product Moment Correlation. Reliability tests using Cronbach's Alpha technique and Normality tests using Kolmogorov Smirnov One-Sample Test. To test the hypothesis using Independent sample t-test. Based on the results of hypothesis testing showed that the expectation gap between auditors of BKM with financial statement users in terms of independence, auditor competency, role and responsibilities of auditors. Auditor BKM have a higher perception in terms of independence, Auditor Competency, Role and Responsibilities of Auditors compared to financial statement users of BKM. Keywords: expectation gap, perception, auditors, financial statement users, independence, auditor competencies, role and responsibilities of auditor.